Evaluation of the effect of artificial re-gassing of aluminium melts after ultrasonic treatment. (2nd January 2017) - Cziegler, A.K.; Pabel, T.; Habe, D.; Schumacher, P.
Abstract: Ultrasonic treatment of aluminium melts is known as an efficient process to remove dissolved hydrogen. Whereas the degassing efficiency of ultrasonic treatment has been extensively reported, the effect of re-gassing after the ultrasonic treatment is much less studied. The present investigation attempts to evaluate the effect of artificial re-gassing of aluminium melts after ultrasonic treatment was applied. The results show an increase in porosity after artificial re-gassing after ultrasonic treatment compared to artificial gassing before the ultrasonic treatment was applied. An increase in potent nucleation sites for gas porosity after ultrasonic treatment by unfolding and/or break-up of bifilms is supposed.